2021
DOI: 10.1002/rmv.2302
|View full text |Cite
|
Sign up to set email alerts
|

Global molecular prevalence and genotype distribution of Sapovirus in children with gastrointestinal complications: A systematic review and meta‐analysis

Abstract: Sapovirus (SaV) is an emerging cause of children gastrointestinal complications such as acute gastroenteritis (AGE). The aim of the present systematic review and metaanalysis was to estimate the global prevalence of the SaV in children and association of infection with SaVs and AGE in children based on case-control studies. Four international databases (PubMed, Scopus, Web of Sciences and Google Scholar) were used to retrieve English-language studies published between January 2000 and December 2020. Comprehens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 198 publications
1
12
0
Order By: Relevance
“…Rapid progressions in sequencing technologies, bioinformatics, and metagenomic have led to the discovery of new viruses in recent years. However, while some studies stated the isolation of new viruses from fecal samples of patients with GE, there is still no solid evidence of the association of these viruses with GE ( 4 , 52 , 53 ). They are often neglected in epidemiological studies as they cause milder or asymptomatic infection, and researchers have a higher tendency to detect common enteric viruses and other infectious agents in patients with GE ( 54 56 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid progressions in sequencing technologies, bioinformatics, and metagenomic have led to the discovery of new viruses in recent years. However, while some studies stated the isolation of new viruses from fecal samples of patients with GE, there is still no solid evidence of the association of these viruses with GE ( 4 , 52 , 53 ). They are often neglected in epidemiological studies as they cause milder or asymptomatic infection, and researchers have a higher tendency to detect common enteric viruses and other infectious agents in patients with GE ( 54 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…While GE is known as a prevalent disease in children younger than 5 years of age and common enteric viruses such as RoV and NoV are mostly found in this age group ( 64 , 65 ), interestingly, our analysis showed that these viruses are more prevalent in older patients. These results might be due to reason that outdoor activities further expose people to viral agents ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Human sapovirus (SV) as one of the leading causative agents of diarrhoea in young children is becoming notable worldwide [ 1 , 2 ]. Information on the distribution of SV genotypes can give insights into the patterns of probable transmission, immunity amongst exposed people, relevant diagnosis of the circulating strains, and development of vaccine to regulate or eradicate virulent strains [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Information on the distribution of SV genotypes can give insights into the patterns of probable transmission, immunity amongst exposed people, relevant diagnosis of the circulating strains, and development of vaccine to regulate or eradicate virulent strains [ 3 ]. Human SV has four well-known genogroups, namely, genogroups I, II, IV, and V. Although SV-GI is the most detected genogroup followed by SV-GII, these genogroups are commonly associated with acute gastroenteritis across age groups and often detected in infants [ 2 , 4 – 8 ]. There are few studies on the detection of human SV in South Africa which have been reported in different settings, that is, on rural outpatients [ 9 ], in a longitudinal study [ 10 ], on urban hospitalized children [ 11 , 12 ], and on all age groups [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation